PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL), UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS X SMA NEGERI 2 LUBUK PAKAM - Pratiwi, Adinda Handayani; Siregar, Disna Anum (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
The background of this research focuses on the low motivation of students to learn in class X of SMA Negeri 2 Lubuk Pakam. This is due to the teaching method that tends to be teacher-centered, so that students are less actively involved in the learning process. This results in students having little opportunity to actively engage in learning activities in the classroom. This research aims to increase students' learning motivation through the application of the Project Based Learning (PJBL) learning model. By using this approach, it is hoped that students can be more engaged and motivated in their learning process. This research study discusses a Class Action Research (PTK). This research has been carried out through two (2) different cycles. In this study, the researcher used data collection instruments in the form of teacher and student observation sheets. In addition, questionnaires are also provided for students to fill out in each research cycle. The collected data is then analyzed using a descriptive quantitative method, which aims to calculate the percentage success rate of an action. Data analysis showed that there was a significant increase in learning in the field of PPPKn Studies among students in each cycle analyzed. The average percentage of scores obtained from the students' observation sheets showed an increase, namely in the first cycle an average score of 53.71% was obtained and in the second cycle there was an increase of 83.42%. The results of the questionnaire answered by students in the first cycle obtained a score of 57.64% and in the second cycle there was an increase of 90%. It can be concluded that the application of the Project Based Learning (PJBL) learning model has proven to be effective in increasing student learning motivation in class X of SMA Negeri 2 Lubuk Pakam.